Solidarity through difference: Speculative participatory serious urban gaming (SPS-UG). (June 2020) - Beattie, Hamish; Brown, Daniel; Kindon, Sara
This article discusses the methodology and results of the Maslow's Palace workshops project, which engages with current debates surrounding the democratisation of digital urban design technology and stakeholder decision making, through the implementation of a speculative oriented approach to serious gaming. The research explores how serious games might be used to help marginalised communities consider past, future and present community experiences, reconcile dissimilar assumptions, generate social capital building and design responses and prime participants for further long-term design engagement processes through a new approach called Speculative Participatory Serious Urban Gaming. Empirical material for this research was gathered from a range of case study workshops prepared with three landfill-based communities and external partners throughout 2017. Results show the approach helped participants develop shared norms, values and collective understandings of sensitive topics and develop ideas for future action through 'collective tinkering'.